Efficacy in predicting mortality of patients with heart failure using heart rate before intensive care unit discharge: a retrospective cohort study from MIMIC-IV Database - Hsiao, Chia-Ying; Su, Min-I; Chang, Yu-Cheng; Lee, Ying-Hsiang; Lin, Po-Lin; Chiou, Wei-Ru (BMJ open, 2024)
ObjectiveHeart rate serves as a critical prognostic factor in heart failure (HF) patients. We hypothesise that elevated heart rate in critically ill HF patients on discharge from the intensive care unit (ICU) could be linked to adverse outcomes.DesignA single-centre retrospective cohort study.SettingThis study used data collected between 2008 and 2019 from the Medical Information Mart for Intensive Care IV (V.2.0) Database.ParticipantsFrom the 76 943 ICU stays, we enrolled 2365 patients in this study.Primary and secondary outcome measuresWe observed correlations between in-hospital mortality and ICU discharge heart rate of 83.56±15.81 beats per minute (bpm) (survivors) vs 93.84±17.28 bpm (non-survivors, p<0.001). Total mortality showed similar trends, with 83.67±15.36 bpm (survivors) vs 85.23±17.25 bpm (non-survivors, p=0.027), as did ICU readmissions at 83.55±15.77 bpm (non-readmitted) vs 88.64±17.49 bpm (readmitted, p<0.001).ResultsGiven multivariate analysis, the ICU discharge heart rate strongly predicted in-hospital mortality (HR 1.032 (95% CI 1.022 to 1.041), p<0.001), total mortality (HR 1.008 (95% CI 1.004 to 1.013), p<0.001) and ICU readmission (HR 1.018 (95% CI 1.010 to 1.025), p<0.001). Patients with an ICU discharge heart rate>90 bpm demonstrated significantly higher in-hospital mortality (HR 2.639 (95% CI 1.898 to 3.669), p<0.001), total mortality (HR 1.342 (95% CI 1.163 to 1.550), p<0.001) and ICU readmission rates (HR 1.781 (95% CI 1.413 to 2.243), p<0.001).ConclusionThe findings suggest that HF patients with an elevated heart rate (>90 bpm) at ICU discharge are more likely to experience increased in-hospital mortality, total mortality and ICU readmissions, indicating potential negative outcomes.